Pengaruh Penggunaan Teknologi Informasi, Sistem Pengendalian Internal, dan Penyajian Laporan Keuangan Terhadap Akuntabilitas Pengelolaan Keuangan Desa(Studi Kasus pada Seluruh Pemerintah Desa di Kecamatan Polanharjo) - Husain Arkanuddin; Dorothea Dorothea (Teewan Journal Solutions, 2025)
Accountability for village financial management is important for stakeholder decision making in regional governance. This study explores the dimensions of financial accountability, the importance of transparent reporting, and compliance with standards. The aim of the research is to determine the influence of information technology, control systems and presentation of village financial reports in Polanharjo District. This research is a survey of village government officials in all Polanharjo sub-districts. The type of data used is quantitative. The data source used is primary data. The population in this research are village officials whose duties are important in managing village finances. The number of samples in this research was 126 village government officials throughout Polanharjo sub-district. The sampling and data collection technique in this research used a questionnaire. Data analysis uses multiple linear regression tests, t tests, F tests and coefficient of determination tests. The results of this research show that the use of information technology, internal control systems, and presentation of financial reports have a significant effect on the accountability of village financial management.